THE ANALYSIS OF FORM IN OSCAR WILDE’S THE PICTURE OF DORIAN GRAY - Diana Fransisca Rompas; Theresia Cicik Sophia Budiman (Universitas Stikubank (UNISBANK) Semarang, 2009)
The study analyzes the form in Oscar Wilde’s novel The Picture of Dorian Gray through point of view, character, and symbol. Point of view is analyzed by using categories of point of view (third or first person narrator). In analyzing character, it will use discursive and dramatic method, and in analyzing symbol, it will find a person, object, action, place, or event that, in addition to its literal meaning, suggests a more complex meaning or range of meanings. After analyzing those elements, this study finds the form by looking the pattern that lies in those elements. Key words: form, point of view, character, symbol.